Fun Classroom: How Seven Graders and Science Teachers Respond to STEM Learning as the First Experience in Suburban Area? - Permanasari, A.; Rubini, B.; Pursitasari, I. D.; Nurramadhani, A.; Hadiana, D.; Suwarma, I. R.; Kumano, Y. (Jurnal Pendidikan IPA Indonesia, 2024)
STEM learning is now being implemented at science schools. After a STEM training session, a group of science teachers in West Java implemented STEM learning in secondary school, a heat and energy topic. The school where STEM learning is implemented is in the suburban area of West Java, Indonesia. The research aims to elaborate on how STEM learning can lead students to learn actively and interactively by using all their modalities as expected by the Merdeka Belajar curriculum. The qualitative research was conducted through profound learning observation. The impact of learning with the STEM approach was then investigated through the STEM Literacy of students. The observation was done directly by some science teachers, and video recording was used to complete the observation. The tests were also conducted to determine the quantitative picture of student achievement (STEM literacy assessment). The results of interviews with teachers and students revealed that this STEM learning was their first experience. Many interesting things were found during the learning process, which significantly provided prospects for the future of STEM learning. STEM learning does not necessarily improve student learning outcomes as expected. However, the characteristics of STEM learning in accelerating the Merdeka Belajar program are evident. All teachers involved agreed that if this learning was applied to at least three more topics, they were optimistic that students could achieve STEM literacy.